Structural optimization and analysis of surface acoustic wave biosensor based on numerical method - Zhaoming Zhou; Jinsong Tan; Jia Zhang; Mian Qin (International Journal of Distributed Sensor Networks)
The biosensor based on surface acoustic wave is of great significance for the application of biological clinical detection, but the sensitivity and specificity of surface acoustic wave biosensor still need to be improved. In this article, the structure of surface acoustic wave biosensor and interdigital transducer is designed by studying the theoretical model of surface acoustic wave biosensor. Then the amplitude–frequency response of the device is studied. Later, the simulation model of surface acoustic wave biosensor structure is established, and the performance of surface acoustic wave device is numerically calculated. Meanwhile, the relationship between the applied excitation signal and the resonant frequency is considered, and the performance of the surface wave propagation and attenuation characteristics are analyzed. In addition, the influence of the material of the piezoelectric substrate and the structure of the interdigitated electrode on the surface acoustic wave propagation are studied. The response potential curve and the total displacement of the particle vibration are analyzed, and the structure of the surface acoustic wave device is optimized.